Pengaruh Kepuasan Pelanggan Terhadap Loyalitas Pada Toko Irma Jaya Kecamatan Taliabu Utara: The Effect Of Customer Satisfaction On Loyalitas At The Irma Jaya Store Taliabu Utara District - Sufri Lasalimu; Ichsan Milang (Jurnal Ilmiah Produktif, 2022)
Customer satisfaction is the level of consumer feelings after comparing what has been received and expectations. The sampling technique in this study is snowball sampling with a sampling period of 1 month which produces a sample of 100 respondents. This study aims to determine whether there is an effect of customer satisfaction on loyalty to the Irma Jaya store. The results of this study obtained a simple regression model obtained a simple regression equation, namely: Y = 0.699 + 0.823X The constant value is 0.699, this can be interpreted as if it is not influenced by the independent variable, namely customer satisfaction, then customer loyalty is 0.699. The regression coefficient value for the customer satisfaction variable is 0.823, meaning that if the customer satisfaction variable increases by one unit, the customer satisfaction variable will increase by 0.823 units. The close relationship between the customer satisfaction variable and the customer loyalty variable is in the very strong category, and the contribution of the customer satisfaction variable to the customer loyalty variable is 67.7%, while the remaining 32.3% is influenced by other variables not included in the study. Based on the research results obtained through calculations using SPSS assistance, the t-count value is 14,326> the t-table value of 1.66 with a probability value of 0.000 <0.05, this implies that the variable customer satisfaction affects customer loyalty at the Irma Jaya store. North Taliabu District, Taliabu Island Regency